Optimization of an analytical method for carbaryl and chlorpyrifos residues determination by LC-MS/MS (Asian-Australasian Journal of Bioscience and Biotechnology, 2022)
The present study was aimed to optimize an analytical method for the quantification of carbamate and organophosphorus insecticide residues using Liquid Chromatography tandem Mass Spectrometry (LC-MS/MS). A series of experiments were conducted to select the parent ion and precusor ion and based on these findings, the analytical method for the determination of carbamate and organophosphorus insecticide residues using LC-MS/MS was developed. The electrospray ionization (ESI) mode was used to develop the method.  The linearity of the developed analytical method was very good and it was 0.999 for carbaryl, while it was 0.998 for chlorpyrifos. The optimization of MS/MS parameters has been done properly for both of the selected pesticides through direct infusion of 100 ug/L pure analytical standard solutions.Asian Australas. J. Biosci. Biotechnol. 2022, 7 (3), 107-113